SINGULARITY DEVELOPMENT IN MOVING-BOUNDARY PROBLEMS - Howison, S; Ockendon, J; Lacey, A (1985)
Singularity development is considered for a class of Stefan moving-boundary problems. Conformal mapping methods are used to construct explicit solutions when the specific heat is zero and these solutions are used to describe singularity development for more general problems in two and three space dimensions. © 1985 Oxford University Press.